Neoliberalism in academia: reflections from a parasitologist - Robin B. Gasser (Parasites & Vectors)
Abstract This article examines the major transformation within the higher education sector, specifically the shift from traditional academia to neoliberal academia, with an emphasis on its impact on academics who entered the field in the 2000s. Many of these individuals may not fully recognise the extensive political and structural changes driven by neoliberalism over the past 2 decades. Published literature shows how the widespread adoption of managerialism in a neoliberal context—particularly in the Anglo-Saxon world—has markedly altered the academic landscape. This shift has led to the marketisation of education, characterised by increased student tuition fees, performance metrics and a change in academic values, including professional autonomy and academic freedom. The present article further explores how these alterations have affected the wellbeing of academics, particularly early- and mid-career scholars, by institutions prioritising economic efficiency over intellectual enquiry, increasing administrative workloads and promoting a consumerist model of education. Drawing on both evidence from the peer-reviewed literature and experiences, the implications of these changes for academic careers, job satisfaction and the broader mission of universities as centres of scholarship and public service are discussed. The article concludes with a call to action for academic leaders and policymakers to recognise and address challenges posed by neoliberalism and managerialism, emphasising the need to support and protect the core values of academia in the face of ongoing changes. Graphical Abstract